Unlearning as resistance and justice: Toward healing and transforming - Sabaheta, Ramcilovic-Suominen (Elsevier, 2025)
Multi-trans- and inter-disciplinarity, while important, cannot on their own ensure ontological and epistemic justice or facilitate transformations to justice, sustainability and thriving for all. We need to recognize, problematize, and eventually willfully and consciously let go of the harmful ontological and philosophical assumptions and myths underlying Western science and epistemology. The ontologies and philosophies inform and shape stories we tell, worldviews, values and beliefs we hold, which further shape our actions, habits and behaviours that we are caught in and reproduce. Thus ontological and philosophical views and asumptions inform and guide our day-to-day ways of living, existing, resisting, relating, caring, or not caring. Increasingly scholars of socioecological transformations recognize the importance of ontologies and philosophies in guiding our individual and collective responses to the metacrises, calling for ontological and relational shifts as key to socioecological transformations. This requires questioning, reflecting and deconstructing the harmful ontological bases of modern Western science and knowledge systems, which fine tune our lenses through which we see the world and act accordingly. I refer to this process as a ‘deep transformative Unlearning’. I frame it as a precondition for both, holding space for the existing invisiblized ontologies, epistemologies and worldviews, and for cultivating new ontological and philosophical emergences. As we start to question and let go, we take with us the wisdom of the old ways, while making space for the new ways to emerge. Unlearning harmful ontologies and associated worldviews, assumptions, and myths that uphold the Western science and the (neo)colonial-capitalist ideas-structures is a matter of justice, survival, and healing.
Keywords: unlearning; relationality; nonduality; intraconnectedness; ontoepistemic (in)justice; modernity-coloniality